Income inequality and economic growth: decomposing the effects of the income distribution - Ioffredi, Marco (Luxembourg, 2018)
"The Occupy Wall Street events of 2011 resurfaced the issues of wealth and income inequality for North American‟s and the world. To understand the economic impacts of divisive income distributions and the specific effects from particular income groups, this paper endeavours to revisit the work of Voitchovsky (2005). By applying the same panel techniques, extending the sample period, and controlling for inequality between the top one percent and the top ten percent, the research gives a sense of the robustness of the short-run relationship between growth and income inequality. The results suggest that the relationship is sensitive to instrumentation, in number and choice; and, the relationship is insignificant across all experiments."